ANALISIS RISIKO PRODUKSI CABAI MERAH DI DESA MARGOTOTO KECAMATAN METRO KIBANG KABUPATEN LAMPUNG TIMUR - Ainul Mardliyah; Priyadi Priyadi (Politeknik Negeri Lampung, 2021)
This research to analyze the risk of red chili production in Margototo Village Metro Kibang District East Lampung Regency. This research was conducted in Margototo Village Metro Kibang District East Lampung Regency. Methods Sampling was conducted using a simple random sampling method. With a sample of 37 farmers who participate in farmer groups that cultivate red chili. This research was conducted from December 2020 to January 2021. Coefficient of Variation (CV) analysis were used t answer. The results showed that the production risk of red chili farming in Maragoto Village Metro Kibang District East Lampung Regency had a low risk with a coefficient of variation for production risk of 0.31.